2009
DOI: 10.1177/0267659109352114
|View full text |Cite
|
Sign up to set email alerts
|

Outcomes comparison of 5 coated cardiopulmonary bypass circuits versus an uncoated control group of patients undergoing cardiac surgery

Abstract: We compared all 5 coated circuits approved for clinical use in Canada against an uncoated control circuit. Three of the 5 coated circuits (Trillium, Phisio and Bioline BCC) were found to improve ventilator and ICU time compared to Control. Further studies are indicated to validate these results and their impact upon approval criteria, purchasing choices and safe clinical practice, especially as applied to higher risk diabetic patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0
1

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 24 publications
0
8
0
1
Order By: Relevance
“…Another study by Marcoux et al. investigating five different coated surfaces underscored that X‐coating CPB correlated with hs‐CRP levels similar to those after the uncoated CPB and that X‐coating failed to achieve shorter ventilation time or ICU length of stay compared with the uncoated circuits (23). The same study showed that X‐coating achieved the worst clinical results—when compared with the other four different coating technologies—in terms of transfusion requirements, intubation time, and ICU length of stay (23).…”
Section: Discussionmentioning
confidence: 97%
“…Another study by Marcoux et al. investigating five different coated surfaces underscored that X‐coating CPB correlated with hs‐CRP levels similar to those after the uncoated CPB and that X‐coating failed to achieve shorter ventilation time or ICU length of stay compared with the uncoated circuits (23). The same study showed that X‐coating achieved the worst clinical results—when compared with the other four different coating technologies—in terms of transfusion requirements, intubation time, and ICU length of stay (23).…”
Section: Discussionmentioning
confidence: 97%
“…The use of PEO is commercially available as part of the Trillium package on Medtronic tubing. Studies using the Trillium surface have shown reductions in inflammatory markers and reduced bleeding events [38][39][40], but also increased stroke rates [38] from cardiopulmonary bypass. Like most CPB studies, these are small, single-center studies with variable sample collection, and no long-term studies have been performed.…”
Section: Polyethylene Oxide (Peo)mentioning
confidence: 99%
“…Like other coatings, PMEA-coated systems have improved markers of inflammation and some clinical outcomes over non-coated systems [44,45]. However, several studies have demonstrated increases in ventilator times, chest tube output, and inflammatory markers of PMEA compared to other coatings [39,46,47], while others studies found little or no difference between PMEA and heparin-coated surfaces [44,48].…”
Section: Poly 2-methoxyethylacrylatementioning
confidence: 99%
“…Clinical outcomes are under investigation and, indeed, part of the study has been published recently. 3 More data of the impact of different coating CPB on renal function, bleeding, atrial fibrillation, neurofunction, and length of hospital stay will be released shortly.…”
mentioning
confidence: 99%